2014
DOI: 10.3171/2013.9.spine13274
|View full text |Cite
|
Sign up to set email alerts
|

Discharge dispositions, complications, and costs of hospitalization in spinal cord tumor surgery: analysis of data from the United States Nationwide Inpatient Sample, 2003–2010

Abstract: Object The aim of this study was to analyze the incidence of adverse outcomes and inpatient mortality following resection of intramedullary spinal cord tumors by using the US Nationwide Inpatient Sample (NIS) database. The overall complication rate, length of the hospital stay, and the total cost of hospitalization were also analyzed from the database. Methods This is a retrospective cohort study conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
76
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 19 publications
5
76
0
1
Order By: Relevance
“…Among those articles, hospitalization costs range widely secondary to the variability in the procedures performed, pathologies treated, and geographic location (such as different countries). 9,12,34,41,44 None of the available studies evaluate and compare the cost of both primary and metastatic spinal tumors. There are several articles that have examined the health care utilization and cost associated with the management of general bony metastasis and its associated "skeletal events," with some providing a subanalysis of spinal column metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among those articles, hospitalization costs range widely secondary to the variability in the procedures performed, pathologies treated, and geographic location (such as different countries). 9,12,34,41,44 None of the available studies evaluate and compare the cost of both primary and metastatic spinal tumors. There are several articles that have examined the health care utilization and cost associated with the management of general bony metastasis and its associated "skeletal events," with some providing a subanalysis of spinal column metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…34 Overall, between 2003 and 2007, the average cost of surgery was $61,157. Interestingly, the cost in 2003 ($45,452) was significantly lower than in 2007 ($76,698).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of tumors of the spinal column is estimated to be 0.62 per 100,000 individuals in the US. 33,85 Metastatic spinal tumors make up the majority of spinal tumors and are found in as many as 70% of cancer patients. 48,52,65,74,86,93,98 In addition to classification by histology, spinal tumors are generally stratified by location as extradural, intradural extramedullary, or intramedullary.…”
mentioning
confidence: 99%
“…To this effect, our data show that patients with private insurance had a lower 57 found that age greater than 64 years had an increasingly significant association with postoperative adverse outcome. Sharma et al 61 also observed a higher likelihood of an adverse event in middle-aged and elderly patients after SCT surgery. This quantification of the observed association of advancing age and adverse outcomes in our study, although critical for decision making, should not deter elderly patients with an optimal risk profile from undergoing benign intradural tumor surgery.…”
Section: Discussionmentioning
confidence: 92%